Randomized Controlled Trials of Zhigancao Decoction Combined With Metoprolol in the Treatment of Arrhythmia: A Systematic Review and Meta-Analysis - Yang, Yan; Ge, Fei-Lin; Huang, Qian; Zeng, Rui; Zhang, Xin-Yue; Liu, Ping; Luo, Gang; Yang, Si-Jin; Sun, Qin (Frontiers in Cardiovascular Medicine, 2022)
Objective: Arrhythmia is a major public health problem worldwide. Numerous studies have shown that this disease is often treated with a combination of traditional medicine (TM) and conventional medicine (CM), however, its effectiveness and safety remain controversial. In order to provide guidance for clinical medication, we analyzed the safety and effectiveness of Zhigancao decoction (ZGCD) combined with metoprolol in the treatment of arrhythmia. Methods: Systematic searches for RCTs were conducted in eight databases (January 2010 to September 2020) without language restrictions. According to the Cochrane system evaluation method, the overall effectiveness and safety were analyzed by Meta with Review Manager software (version 5.3), and publication bias was qualitatively analyzed using STATA 12.0. Results: A total of 39 RCTs were included, including 4260 patients with arrhythmia, with 2133 patients in the experimental group and 2127 patients in the control group. Meta-analysis showed that compared with metoprolol alone, ZGCD combined with metoprolol could significantly increase the total efficacy(OR=4.74, 95% CI: 3.78~5.94, P<0.01), and lower the incidences of arrhythmia(MD=-3.39, 95% CI:-4.09~-2.68, P<0.01). Moreover, the HR were slow down in the experimental group(MD=-8.48, 95% CI:-10.98~-5.97, P<0.01) and the Traditional Chinese medicine (TCM) symptoms were obviously improved than control group (MD=-2.92, 95% CI: -3.08–-2.76, P<0.01). Besides, the incidence of adverse events was reduced (RR=0.36, 95% CI: 0.26–0.51, P<0.01). Further subgroup analysis of different types of arrhythmia showed that the results were consistent with the above, that is, the total efficacy of the experimental group was higher, and there were fewer adverse events. Conclusion: ZGCD combined with metoprolol has good efficacy and fewer adverse reactions for arrhythmias of different pathological types, so this method can be considered as a worthy complementary and alternative therapy.